Adolescent self-harm and suicide attempts: An analysis of emergency department presentations in Singapore - Darren Kai Siang Chong; Vicknesan Jeyan Marimuttu; Pei Shan Hoe; Chu Shan Elaine Chew; Angelina Su Yin Ang (Annals, Academy of Medicine, Singapore)
Introduction: The rising rate of adolescent suicide, and the burden of self-harm and mental health disorders, pose significant threats to Singapore’s future health outcomes and human potential. This study sought to examine the risk profile and healthcare utilisation patterns of Singaporean adolescents who presented to the emergency department (ED) for suicidal or self-harm behaviour. Method: A retrospective review of medical records for patients aged 10 to 19 years who visited Singapore’s KK Women’s and Children’s Hospital ED for suicidal or self-harm attempts from January to December 2021 was conducted. Results: A total of 221 patients were identified, with a predominance of female patients (85.5%) over males (14.5%). The mean age was 14.2 ± 1.4 years. Intentional drug overdose (52.0%) was the most commonly used method. Significantly more females presented for intentional paracetamol overdose (46.6% versus [vs] 28.1%, P=0.049), whereas jumping from a height was more common among males (18.8% vs 5.8%, P=0.022). The most frequently observed mental health challenges were stress-related and emotional coping difficulties (50.7%), followed by mood and anxiety symptoms (53.4%). A history of self-harm and suicidal behaviours were the most common psychosocial risk factors. Within the year prior to their ED presentation, 15.4% had accessed healthcare services for mild medical ailments, 19.5% for medically unexplained symptoms, and 17.2% for previous self-harm or suicide attempts. Conclusion: Most cases involved psychosocial and emotional regulation difficulties, some of which displayed sex-specific patterns, rather than complex psychiatric disorders. The identified predictive factors can help inform Singapore’s National Mental Health and Well-being Strategy, to guide targeted and transdiagnostic interventions in schools and community settings.